2021
DOI: 10.1002/slct.202004001
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Approaches for Building the C14‐C21 Fragment of Eribulin

Abstract: Herein, we report a practical stereoselective synthesis of C14-C21 and C15-C21 tetrahydrofuran-based fragment of eribulin using two different approaches. The approach utilizes iodoe-therification and intra molecular oxa-Michael additions as key steps in individual approaches using R,R-tartaric acid and Lascorbic acids as cost effective chiral starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Later, they optimized the synthesis of 3 via multiple asymmetric Cr-mediated coupling reactions, , and the last coupling required a key intermediate 4 as the C14–C23 fragment to couple with diiodide 5 . Till date, several synthetic studies toward these fragments have also been revealed. However, it is still necessary to develop a more concise route with easier purification and higher yields for large-scale preparation of anti-cancer drug eribulin at low cost. Herein, we report a synthetic route to intermediate 4 from cheap l -arabinose, highlighted by an α-stereospecific C -glycosylation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Later, they optimized the synthesis of 3 via multiple asymmetric Cr-mediated coupling reactions, , and the last coupling required a key intermediate 4 as the C14–C23 fragment to couple with diiodide 5 . Till date, several synthetic studies toward these fragments have also been revealed. However, it is still necessary to develop a more concise route with easier purification and higher yields for large-scale preparation of anti-cancer drug eribulin at low cost. Herein, we report a synthetic route to intermediate 4 from cheap l -arabinose, highlighted by an α-stereospecific C -glycosylation reaction.…”
Section: Introductionmentioning
confidence: 99%